Occurrence of filamentous fungi in yerba mate discarded in the environment - Klotz-Neves, Ana Luiza; Bertazzo-Silva, Fernando Augusto; Maggio, Lilian; Heberle, Marines de Avila; Baptista, Vanessa dos Anjos; Putzke, Jair (Revista de Ciencias Agrícolas, 2022)
Yerba mate, Ilex paraguariensis A. St. Hil. (Aquifoliaceae), waste is one of the most common byproducts generated in households in southern Brazil due to the traditional consumption of mate. However, the decomposition of this waste by fungi has not been thoroughly evaluated. In order to study the fungal succession in mate residue, 450 samples were evaluated during the autumn, winter, and spring, and kept for two months in a humid chamber (aerobic medium) for the growth of associated filamentous fungi. We morphologically identified the fungi by means of a microscopy device and taking into consideration only the surface-developed mycelia. Twenty-two genera of filamentous fungi were found, of which the Zygomycota (Rhizopus spp. and Mucor spp.) microflora deserve special attention since they were the only fungi growing in the first 19 days. After this period, the fungi Deuteromycota (mainly Aspergillus spp.) and Oomycota (Pythium spp.) develop more vigorously, supplanting the previous ones. The species of Curvularia, Fusarium, Verticillium, and Pythium are phytopathogens and end up having their inoculum source increased with the irregular disposal of this residue in nature. The presence of numerous fungal genera, which are known to be pathogenic according to the literature, highlights the importance of implementing proper waste disposal practices in the environment. Improper disposal of the yerba mate waste can result in contamination not only of yerba mate itself but also of other commercial crops. Therefore, it is imperative that greater attention be paid to the disposal of this waste.